Ionic-Liquid-Based Paclitaxel Preparation: A New Potential Formulation for Cancer Treatment - Chowdhury, M.R. (American Chemical Society, 2018)
Paclitaxel (PTX) injection (i.e., Taxol) has been used as an effective chemotherapeutic treatment for various cancers. However, the current Taxol formulation contains Cremophor EL, which causes hypersensitivity reactions during intravenous administration and precipitation by aqueous dilution. This communication reports the preliminary results on the ionic liquid (IL)-based PTX formulations developed to address the aforementioned issues. The formulations were composed of PTX/cholinium amino acid ILs/ethanol/Tween-80/water. A significant enhancement in the solubility of PTX was observed with considerable correlation with the density and viscosity of the ILs, and with the side chain of the amino acids used as anions in the ILs. Moreover, the formulations were stable for up to 3 months. The driving force for the stability of the formulation was hypothesized to be the involvement of different types of interactions between the IL and PTX. In vitro cytotoxicity and antitumor activity of the IL-based formulations were evaluated on HeLa cells. The IL vehicles without PTX were found to be less cytotoxic than Taxol, while both the IL-based PTX formulation and Taxol exhibited similar antitumor activity. Finally, in vitro hypersensitivity reactions were evaluated on THP-1 cells and found to be significantly lower with the IL-based formulation than Taxol. This study demonstrated that specially designed ILs could provide a potentially safer alternative to Cremophor EL as an effective PTX formulation for cancer treatment giving fewer hypersensitivity reactions. Â© 2018 American Chemical Society.